Bacillus thuringiensis strains isolated from Qatari soil, synthesizing δ-endotoxins highly active against the disease vector insect Aedes aegypti Bora Bora. Issue 10 (October 2020) - Nair, Kavita; Al-Thani, Roda; Ginibre, Carole; Chandre, Fabrice; Alsafran, Mohammed; Jaoua, Samir
Abstract: Bacillus thuringiensis (Bt) is a Gram-positive soil bacterium that has been recognized as an effective bioinsecticide active against plant, animal and human pathogenic and disease vector insects. During its sporulation phase, Bt produces crystals consisting of δ-endotoxins, which upon ingestion kill specifically insect larvae. Bt subsp. israelensis ( Bti ) is very active against dipteran insects. Bti based bioinsecticides are considered as a sustainable solution to control the Dipteran insects responsible of plant, animal and human diseases. In this study, Bti strains isolated from Qatar soil were analyzed for their insecticidal activities against the dipteran insect Aedes aegypti Bora Bora ( Culicidae, Diptera ) and for their δ-endotoxins yields per cell. Among the local Bti strains, four exceptional strains producing spherical crystals, were found to be more insecticidal than the reference strain Bti H14. When tested for their δ-endotoxin yield, the Bti QBT217 strain, producing typical spherical crystals and having the best insecticidal activity, was recognized as the best candidate strain for potential bioinsecticide production and biological control of dipteran insects, particularly the disease vector insect A. aegypti . Abstract : Agricultural science; Microbiology; Environmental science; Food safety; Epidemiology; Infectious disease; Bacillus thuringiensis subsp. israelensis ; Aedes aegypti Bora Bora ; Insecticidal; Bioassay; δ-endotoxin production.